Potensi Antiseptik Beberapa Jenis Sabun Pada Tangan Penjamah Makanan Jajanan (Studi Kasus: Kantin Poltekkes kemenkes Yogaykarta) - Faraht Lala Ikrima; Adib Suyanto; Muryoto Muryoto (Poltekkes Kemenkes Yogyakarta, 2014)
The decision letter of Health Minister of the Republic of Indonesia Number 942/Menkes/SK/VII/2003 requires food handlers to maintain the cleanliness of their hands by washing them everytime they handling the food with standard hand washing soap. Snacks food handlers in the cafeteria of Polytechnic of Health Yogyakarta have not washed yet their hands with the standardized anti-septic containing soap, so that the hands may still have high microbe number and possible to contaminate the food. This experimental study was aimed to determine the antiseptic potency difference among three types of soap towards the hands of the food handlers by following posttest only with control group design. There were eight respondents and each of their left hands were treated by using two types of soap they usually use (soap L and S) and one brand-newstandardized hand-washing soap (soap D). Total plate number method was used to measure thehand microbe number and then the antiseptic potency was calculated for each soap type. The one way anova test results obtained p value less than 0,05, which means that the antiseptic potency among the soaps was not signifcantly different. However, descriptively, the average of antiseptic potency of soaps L, S and were 41,56 %, 26,30 % and 48.81% respectively. Therefore, the standardized soap D has the highest antiseptic potency.